Ultrafine particles and Particulate Matter₂.₅ assessment in transportation hub, Kuala Lumpur International Airport Terminal 2 (KLIA2), Sepang, Selangor / Muhammad Fahriszaki Paimon - Paimon, Muhammad Fahriszaki (2015)
Ultrafine Particles (UFP) and Particulate Matter z.s (PM₂.₅) are the air pollutants that can seriously be harmful to human once being exposed in long period of time. Vehicle combustion and cooking activities are the particulates potentially sources. The assessment was conducted at taxis and buses waiting area in Transportation Hub, KLIA2, Sepang, Selangor during weekdays and weekday. Main objective of this study is to identify the concentration of UFP and PM₂.₅ in taxis and buses waiting area which being assessed in term of weekdays and weekend, daytime and night time comparison, and also the trend relationship between both of pollutants and other Indoor Air Quality Parameters. This study is referred to UFP and PM₂.₅related journals, TSI Indoor Air Quality Handbook, Guideline on Industry Code of Practice 2010 by Department of Occupational Safety and Health as reference during this study conducted. UFP and PM₂.₅ assessment was conducted via walkthrough inspection, sampling readings of UFP and PM₂.₅, Carbon Dioxide, Carbon Monoxide, Relative Humidity and Temperature in 24 hours represents weekend and weekdays and 4-time slot evenly distributed at sampling area. The instrumentations used for this study were TSI P-Trak Ultrafine Particle Counter Model 8525, Q-Track Indoor Air Quality Monitor Model 7575 and Dusttrak DRX Aerosol Monitor 8534. From the walkthrough inspection, the idle buses were not off the engines while waiting passenger and some occupier smoke near to main entrance to waiting area. Average readings for UFP and PM₂.₅ were 22373 particles/cm³ and 0.188mg/m³ respectively in weekday were higher than average readings 18994 particles/cur' and 0.174 mg/m³ respectively in weekend. There me relationship between UFP and PM₂.₅ and IAQ parameters ( p<0.05). Average readings for UFP and PM₂.₅ were higher in day time 25834 particles/cm³ and 0.101 mg/m respectively than night time 21327 particles/cur' and 0.083 mg/m³ respectively. This UFP and PM₂.₅ assessment showed that the pattern of concentration was influenced by the adherence of passengers, availability of idle taxis and buses and smoking activities. Ventilation control in the area is good but there shall the regulatory control includes engine off policies and closed-smoking room for smokers. This study shall benefit to building proponent as well as academic purposes.